Total fungi profile in dried corn using traditional drying system in Kendal, Central Java Province, Indonesia. Issue 1 (July 2021) - Al-Baarri, A N; Hadipernata, M; Somantri, M; Munarso, J; Rachmat, R; Rahayu, E; Pratiwi, A F; Setyadi, B; Mawarid, A A; Pangestika, W; Lestari, F P
Abstract: Harvesting method is the key factor to receive agriculture product with maximum value on its categories including microbiological content. Recent study exposed the total fungi as the effect from the drying technology in the Kendal, Central Java Province as traditional drying method that has been used in the most field. Harvesting period was done at 100 day of plantation with the following step: reducing the top leaf then followed by drying in the field for 7 days. The corn was obtained from 15 plants in 3 separated areas. The fresh corn was then transferred to the laboratory and analyzed for total fungi. As result, the total of fungi was able to be detected at amount of more than 1 Log CFU/ml. This finding was very important information for the distributor to choose best handling of storage. As conclusion, the total fungi of corn using traditional drying was able to be analyzed and exposed.